x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

24 ビュー (過去 30 日間)
cadburry oreo
cadburry oreo 2020 年 10 月 4 日
回答済み: Jonas 2023 年 2 月 8 日
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

回答 (1 件)

Jonas
Jonas 2023 年 2 月 8 日
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

カテゴリ

Help Center および File ExchangeSystems of Nonlinear Equations についてさらに検索

タグ

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by